Canada_Basin_Zooplankton_2003_2006_Rutzen_Hopcroft - Russell Hopcroft (Arctic Data Center, 2014)
This dataset presents community structure, distribution, abundance and biomass of Zooplankton samples collected from the Canada Basin during the summers of 2003 - 2006 using a 150 um Bongo Net. Unpublished data R.R. Hopcroft and I. Rutzen, University of Alaska Fairbanks